2021
DOI: 10.1002/jctb.6735
|View full text |Cite
|
Sign up to set email alerts
|

Particle size distribution of chemical oxygen demand in industrial effluents: impact on effective filtration size and modelling of membrane bioreactors

Abstract: This study reviews particle size distribution (PSD) analysis for industrial effluents. Evaluation of available experimental data indicated that the approach started with arbitrary selection of size distribution. Following a pioneering study on pulp and paper effluent, sequential filtration and ultrafiltration has established itself as a prescribed methodology complementing respirometric assessment of chemical oxygen demand (COD) fractionation based on biodegradation characteristics. Results indicated that most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Table 6 outlines the PSD profile of COD in this study, along with those of selected industrial effluents 2,19,21,34,41 . Unlike domestic sewage, which is characterized by a limited soluble COD fraction of around 30%, the soluble COD was disclosed as the major COD fraction of industrial effluents; this attribute is quite significant for the application of activated sludge systems operated with membrane filtration modules 22,43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 6 outlines the PSD profile of COD in this study, along with those of selected industrial effluents 2,19,21,34,41 . Unlike domestic sewage, which is characterized by a limited soluble COD fraction of around 30%, the soluble COD was disclosed as the major COD fraction of industrial effluents; this attribute is quite significant for the application of activated sludge systems operated with membrane filtration modules 22,43 …”
Section: Discussionmentioning
confidence: 99%
“…PSD is now utilized to provide a better insight for system design and performance evaluation. Extensive reviews reporting PSD analysis of COD by means of the prescribed methodology (involving sequential filtration and ultrafiltration) provided default results for sewage 21 and these proved to be a new asset for industrial effluents, especially for strong wastes, such as landfill leachate 22 . Efforts are now focused on establishing direct relationships between PSD results, biodegradation characteristics, and COD fractionation for different wastewaters 23‐26 …”
Section: Introductionmentioning
confidence: 99%
“…Nanofiltration of biologically treated P&P effluents was investigated in [42], eventually preceded by microfiltration or ultrafiltration, obtaining a permeate free of color and organic compounds; the nanofiltration concentrate was treated with ozone to improve its biodegradability and reduce lignin and turbidity levels. The importance of COD fractionation to model membrane filtration processes was highlighted in [43], showing that most industrial effluents (as the present one) are characterized by a preponderance of soluble fractions that require a dedicated modeling tool. Overall, ultrafiltration permeates were proved to be reusable in most P&P processes, except for bleaching (due to excessive Ca 2+ concentrations) [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…A major flaw of most experimental studies carried out at the laboratory scale with a synthetic substrate is to ignore the fact that the substrate characteristics have to be associated with a designated wastewater in the field; this association should not only cover the strength in terms of the COD content, but also COD fractionation and particle size distribution with especially the soluble COD to particulate COD ratio ( S T / X T ), which is a crucially important parameter that would determine the magnitude of energy conservation 27 . As in many similar works, 15,16 the study reported in Liang et al 26 .…”
Section: Methodsmentioning
confidence: 99%